RETRACTED: The role of physical education in preserving the integrity of human existence - Byankina Larisa; Manikovskaya Mariya; Stukova Ekaterina (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001